2003
DOI: 10.1128/ec.2.4.798-808.2003
|View full text |Cite
|
Sign up to set email alerts
|

Asexual Development Is Increased in Neurospora crassa cat - 3 -Null Mutant Strains

Abstract: We use asexual development of Neurospora crassa as a model system with which to determine the causes of cell differentiation. Air exposure of a mycelial mat induces hyphal adhesion, and adherent hyphae grow aerial hyphae that, in turn, form conidia. Previous work indicated the development of a hyperoxidant state at the start of these morphogenetic transitions and a large increase in catalase activity during conidiation. Catalase 3 (CAT-3) increases at the end of exponential growth and is induced by different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 49 publications
5
67
0
Order By: Relevance
“…The intracellular concentration of ROS generated by light may have been enhanced by the loss of SOD resulting in a high level of carotenoid accumulation in the early light induction of carotenoid synthesis. Recently, in N. crassa, catalase-3-deficient mutant showed enhanced production of carotenoid synthesis in colonies under illumination (48). These results suggested that intracellular ROS affect light inducible carotenoid synthesis.…”
Section: Light-inducible Carotenogenesis Ismentioning
confidence: 80%
“…The intracellular concentration of ROS generated by light may have been enhanced by the loss of SOD resulting in a high level of carotenoid accumulation in the early light induction of carotenoid synthesis. Recently, in N. crassa, catalase-3-deficient mutant showed enhanced production of carotenoid synthesis in colonies under illumination (48). These results suggested that intracellular ROS affect light inducible carotenoid synthesis.…”
Section: Light-inducible Carotenogenesis Ismentioning
confidence: 80%
“…This indicates that the hyphal CAT-3 activity was not related with their osmotic sensitivity of the os mutants. Although CAT-3 was detected in the cytosol, it could be secreted and bound to the cell walls (Michan et al, 2003). It is possible that the secreted CAT-3 would not bind to an abnormal cell wall, which os mutants might have, and hence would affect the level of the hyphal CAT-3 activity of these mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to hydrogen peroxide of hyphal growth of os and cat mutants It is known that the cat-3 null mutant is sensitive to hydrogen peroxide (Michan et al, 2003). We previously reported that the os-2 mutants was more sensitive to oxidative stress than the wild-type strain .…”
Section: Fludioxonil Induced Cat-3-to-cat-1 Transition In Hyphaementioning
confidence: 99%
See 2 more Smart Citations